Von der „Rose ohne Dornen bis zum Tatra-Abenteuer von Zosia und Franek“. Das Gedächtnis und das Bewusstsein vom Bergraum in den Tatra-Wissenskompendien für Kinder - Anna Pigoń (Góry, Literatura, Kultura)
The first compendia of knowledge about the Tatra mountains addressed to child readers emerged at the beginning of the 20th century. The most important authors in this genre include Bohdan Dyakowski, Jadwiga Roguska-Cybulska and Zofia Urbanowska. According to Pola Kuleczka, her works are characterized by “a tendency to combine the pattern of an adventure story with an encyclopedic-informative layer.” Two recent publications, Tatry. Przewodnik dla małych i dużych [The Tatras: A Guidebook for the Travellers Big and Small] (B. Gawryluk, P. Skawiński, Kraków 2021) or TOPR. Tatrzańska przygoda Zosi i Franka [TOPR: Zosia and Franek’s Adventure in the Tatras] (B. Sabała-Zielińska, Warszawa 2022) can be perceived as a sign of a re-emergence of this genre. Their popularity shows that these peculiar repositories of knowledge associated with the Tatra region are in constant demand, although they form and the goals set for them change over time. This article presents the history of the Tatra-knowledge compendia for children and their functions, particularly as transmitters of memory. The analysis encompasses some of the most important works in this subgenre of children’s literature in order to discuss different aspects of memory in the works discussed.